Prediction of Love Trauma Syndrome Based on Cognitive Emotion Regulation and Early Maladaptive Schemas in Students with Emotional Breakup Experiences - yousefi, niaz; Zargham Hajebi , Majid; tabarraei, Ramin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective:  The present study aimed to predict Love Trauma Syndrome based on cognitive emotion regulation and early maladaptive schemas in students with emotional breakup experiences.Methods and Materials: This research is considered applied in terms of its goal and descriptive-correlational in terms of methodology. The statistical population included all students from Islamic Azad Universities in Tehran. To select the research sample, 206 individuals who scored above the mean on the Love Trauma Syndrome Questionnaire were chosen through convenience sampling. The research instruments included the Love Trauma Inventory (LTI) (Ross, 1999), the Cognitive Emotion Regulation Questionnaire (CERQ) (Garnefski et al., 2001), and the Young Schema Questionnaire–Short Form (YSQ-SF) (Young, 1994). The data were analyzed using Pearson correlation and simultaneous multiple regression analysis.Findings: The findings showed a significant negative relationship between cognitive emotion regulation and Love Trauma Syndrome (P